The Relationship between Maxillary Sinus Lateral Wall Thickness, Alveolar Bone Loss, and Demographic Variables: A Cross-Sectional Cone-Beam Computerized Tomography Study - Talo Yildirim, Tuba (Med Princ Pract, 2019)
OBJECTIVES: Sinus floor elevation and augmentation surgery is widely used as a reliable procedure to increase insufficient bone height in the posterior maxillary area. The purpose of the present clinical study was to determine the associations between periodontal bone loss (PBL), maxillary sinus lateral bone wall thickness, age, and gender using cone-beam computerized tomography (CBCT). MATERIALS AND METHODS: The current retrospective study consists of 716 maxillary sinus CBCT images of 358 patients. The CBCT scans were assessed to detect the relationship between lateral wall thickness and PBL. ANOVA and Student t test analysis were used to determine the influence of PBL on sinus lateral wall thickness. RESULTS: Sinus lateral wall thickness was significantly associated with PBL (p < 0.05) at 3, 13, and 15 mm height. There was no significant association between lateral wall thickness and gender (p > 0.05). However, there was a significant association between lateral wall thickness at 3 and 13 mm and age (p < 0.05). There were significant associations between PBL and age (p < 0.001), and PBL and gender (p < 0.05). CONCLUSIONS: PBL might have an association with maxillary sinus lateral bone wall thickness. Further studies are needed to confirm this possible relationship.